Catalytic effects for cellulose-based model fuels under low and high heating rate in air and oxy-fuel atmosphere. (15th September 2022) - Eckhard, Till; Pflieger, Christin; Schmidt, Stefan; Böttger, Jannik; Senneca, Osvalda; Schiemann, Martin; Scherer, Viktor; Muhler, Martin; Cerciello, Francesca
Graphical abstract: Highlights: Role of AAEM in catalyzing oxy-combustion reactions. Comparison of slow and fast heating rate experiments in oxy-fuel atmosphere. Catalytic activity scale: Fe > K > Na > Mg ∼ Ca as sulfates. Mineral transformation and carbon structural changes influence combustion rate. Abstract: The detailed catalytic influence of minerals on solid biomass in oxy-fuel combustion is yet to be fully understood. The catalytic influence of metal sulfates on a mineral-free, cellulose-based model biomass was investigated during slow and high heating in air and oxy-fuel combustion. Measurements were performed in a thermogravimetric setup in air with slow heating rates and in a flat-flame burner in oxy-fuel combustion atmosphere with high heating rates. Temperature-programmed experiments identified the catalytic activity scale of Fe > K > Na > Mg ∼ Ca in synthetic air (20% O2 /He) for the sulfates. The highly active metals Fe and K were chosen for more detailed investigations in oxy-fuel combustion experiments using an additional loading of Mg as less-volatile mineral tracer. Samples doped with Fe and Mg (FeMg-MH) exhibited lower thermal stability and higher particle combustion temperatures in the flat-flame burner compared with the undoped model fuel, while the combination of K and Mg (KMg-MH) decreased the particle combustion temperature drastically during oxy-fuel combustion. X-ray diffraction patterns acquired between 25 and 800 °C showed that in FeMg-MH the mineral phases FeSO4 and MgSO4 were still separated and independently active, while the addition of MgSO4 to K2 SO4 formed the stable mineral phase Langbeinite inhibiting the K mobility. The influence of metal chlorides and nitrates was also investigated by slow heating rate TGA experiments showing an overlapping of metal salts decomposition and carbon devolatilization and oxidation.